Knowledge and decision making in the choice between caesarean section and vaginal delivery - Nazneen, Sohely; Akter, Dilruba; Mahejabeen; Ferdousi, Shammi Sultana; Debi, Mina Rani; Aryan, Kazi M. Shams (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: The decision-making process regarding the choice between caesarean section (CS) and normal vaginal delivery (NVD) is influenced by various socio-demographic, cultural, and healthcare factors. This study aims to explore these factors among antenatal patients in Bangladesh. Methods: This prospective observational study was conducted at the institute of child and mother health, Matuail, Dhaka, Bangladesh, from January 2023 to June 2023. A total of 200 antenatal patients attending the antenatal care (ANC) clinic were included. Data were collected through structured interviews and medical record reviews, focusing on socio-demographic variables, healthcare access, cultural influences, and perceived safety regarding delivery methods. Statistical analyses included descriptive statistics, chi-square tests, and logistic regression. Result: The majority of participants were aged 21-30 years (68%), predominantly Muslim (93.5%), and from urban areas (62%). Most were homemakers (75%) with secondary (37.5%) or higher secondary education (28%). Economic status showed 78.5% had a monthly income of 10,001-50,000 BDT. Early marriage (≤18 years) was prevalent (44.5%), with 31% having their first pregnancy at or before 18 years. Most pregnancies were planned (80.5%) and spontaneous (89%), with 88% receiving regular antenatal care. Decision-making for delivery methods involved relatives alone (21%) and husbands alone (19%), with 78% preferring NVD and 22% preferring CS. Conclusion: The study reveals that socio-demographic and cultural factors significantly influence delivery method preferences among pregnant women in Bangladesh. There is a need for educational interventions to promote informed decision-making and enhance maternal healthcare services.